PELAKSANAAN STANDAR OPERASIONAL PROSEDUR (SOP) WAITER DAN WAITRESS DI TAMINGSARI TURI BEACH RESORT BATAM - Bakara, : Irnawati Suryani; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Turi Beach Resort is located in a city that is the city of Batam where this location is a lot of favorite locations for tourists in the country and foreign tourists to visit, (1) to know the implementation of Standard Operating Procedures (SOP) of waiter and waitress at Tamingsari Turi Beach Resort Batam (2) to know the constraints encountered in the implementation of SOP waiter and waitress. The design of this study using qualitative methods with descriptive approach in which researchers will retrieve data from informants who know the restaurant in Turi Beach Resort Batam. From the research results can be concluded in the implementation of Standard Oprasional Procedure (SOP) waiter and waitress Mise And Place Table Setting, Greet And Great, Offering Menu, Taking Order, Other Service, Clearing Table, Taking The Dessert Order, Presenting Bill, Clearing and some obstacles that are found are Individual, Leadership, Team and system. Keywords: Implementation, Food And Beverage Service Department